COMMENSAL GUT BACTERIA REGULATE HIF ACTIVITY TO PROMOTE INTESTINAL HOMEOSTASIS. (26th January 2023) - Dowdell, Alexander; Mahjoob, Omemh; Colgan, Sean
Abstract: Inflammatory bowel disease (IBD) is a disorder marked by chronic, relapsing inflammation of the gastrointestinal tract. Although the precise etiology of IBD is unclear, pathogenic immune response to the gut microbiota is considered a contributing factor. The importance of the gut microbiota in the development of intestinal inflammation has been previously shown through associative studies that correlate dysbiosis of the gut microbiota with active IBD, particularly through the loss of fiber-fermenting obligate anaerobes, an increased presence of pathobionts, and an overall decrease in microbial species diversity. Although the gut microbiota clearly plays an essential role in the development and progression of IBD, the mechanisms by which these micro-organisms regulate gut homeostasis remain to be fully elucidated. Previously, we found that Salmonella Typhimurium (STm), a model invasive pathogen, activated hypoxia inducible factor-1α (HIF-1α) in intestinal epithelial cells (IECs) to regulate anti-bacterial autophagy. HIF-1α is a member of a transcription factor family that senses and responds to environmental stressors, in particular low oxygen tensions. Such stressors stabilize HIF-1α in the cytoplasm and prevent its usual oxygen-dependent degradation. Of note, HIF-1α has been previously shown to be essential for intestinal homeostasis in animal models of IBD, and stabilization of HIF has been demonstrated to be protective during various models of colitis in mice. As an extension of these studies, we asked whether bacterial stabilization of HIF was unique to STm in the intestinal epithelium. We found that stabilization of HIF in IECs was not restricted to STm but was, surprisingly, recapitulated by a wide variety of bacteria, including bacteria rendered non-invasive by genetic manipulation and nonpathogenic/commensal enteric bacterial isolates. Further, we observed that stabilization of HIF was dependent on live bacteria and not due to a secreted factor, suggesting an innate HIF response by the intestinal epithelium to enteric bacteria. Finally, we found modulation of HIF signaling by enteric bacteria including regulation of numerous genes previously implicated in gut homeostasis. These results, taken together, suggest that commensal bacteria regulate intestinal homeostasis through activation of the transcription factor HIF.